Outbreaks of COVID-19 in Medical organizations - Y. I. Sisin; A. A. Golubkova; I. I. Kozlova; N. A. Ostapenko (Эпидемиология и вакцинопрофилактика, 2021)
Relevance. Prevention of the outbreak of a new coronavirus infection in medical organizations (MO) is one of the tasks facing the Rospotrebnadzor service and practical health care. Analysis of the causes and conditions of the spread of SARS-CoV-2 in the MO allows us to determine the most effective measures to contain the infection and prevent the occurrence of subsequent diseases in the focus.The aim is to characterize the epidemiological features of a new coronavirus infection during its nosocomial spread in medical organizations based on the analysis of outbreak incidence.Materials and methods. The data of the reporting forms «General information on patients with positive COVID-19», «General information on patients with community-acquired pneumonia with positive COVID-19» (138 pieces of information), copies of «Acts of epidemiological investigation of foci of infectious (parasitic) diseases with the establishment of a causal relationship» (57 pieces of information), copies of extraordinary reports on an emergency of a sanitary and epidemiological nature (57 pieces of information) were analyzed. The work uses epidemiological and statistical methods of research.Results. When analyzing 57 COVID-19 outbreaks in 30 medical organizations, it was found that the outbreak incidence was more often registered in multidisciplinary hospitals – 70.2% compared to 12.3% in specialized organizations of noninfectious profile, 10.5% of outbreaks were in polyclinics, 1.8% at emergency medical stations. The total number of people affected by the spread of the infection was 961, with a small proportion of children (15 people or 1.7%). Among those who fell ill with the spread of infection in the foci, the share of employees of medical organizations was 62.6%, including doctors – 16.6%, middle and junior medical workers-50.6% and 11.3%, respectively, and other categories – 21.5%. In nosocomial outbreaks of COVID-19, the focality index corresponded to 16.9, and the average duration of the focus was 32.4 days. The construction of the so-called «combined» outbreak diagram in the course of the epidanalysis allowed us to establish its total duration, which was 71 days, with the peaks of morbidity within the outbreak at intervals of 3–7 days, the greatest number of cases in the 1st and 8th days, and the gradual «extinction» of its activity in dynamics.Conclusions. The outbreak of COVID-19 in medical organizations usually occurred when there was an epidemic problem with COVID-19 in the territory. The peculiarity of nosocomial outbreaks was a significant proportion of adults (98.3%), mainly employees of medical organizations, who were often active sources of infection, as well as the involvement of structural units and hospitals for adults in the epidemic process, a high frequency of etiological interpretation of outbreaks (95.9%), a significant proportion of asymptomatic forms of infection and carrier, and the complexity of differential diagnosis of cases of out – of-hospital and nosocomial infection. The patterns of occurrence and spread of morbidity in medical organizations can be used in practical anti-epidemic work.